Nutritional Assessment of Pulps and Partial Characterization of Seed Oils from Varieties of Pear Fruits - Obasi, Nwogo Ajuka; Aloke, Chinyere; Obasi, Stella Eberechukwu; Famurewa, Ademola Clement; Elom, Sunday Oge; Aja, Patrck Maduabuchi; Ajala, Lawrence Olusegun (Journal of Pharmacy and Nutrition Sciences, 2023)
The nutrients and chemical contents of Persea americana, Dacryodes edulis, and Canarium scheinfurthi fruits and partial characterization of their seed oils were carried out to ascertain their nutritional benefits. The fruit pulps were analyzed for chemical (proximate) composition, amino acids profile, vitamins, and phytochemical and anti-nutritional compositions. Oils were extracted from the fruit seeds and the physico-chemical properties of the seed oils were determined according to the standard protocols. The results showed that the fruit pulps contained an abundance of macro- and micro-nutrients which varied significantly (p < 0.05) among the varieties with low anti-nutrients. The essential amino acid contents were high and varied significantly (p < 0.05) among the varieties. Glutamic acid, followed by aspartic acid had the highest concentration of the amino acids, while the concentrations of methionine and cysteine were low in all the varieties. The results also revealed high essential amino acids score values, above 100% for isoleucine and total aromatic amino acids. The physicochemical properties of the fruit oils showed that the oils were edible (low acid value) and may have industrial potential due to their low peroxide, iodine, and saponification values. Overall, the results showed that the pears are nutritionally rich and could serve dietetic and industrial purposes.